PENERAPAN CORPORATE SOCIAL RESPONSIBILITY DALAM PENGELOLAAN WAKAF PRODUKTIF - Masruchin (Program Studi Ekonomi Syariah Fakultas Ekonomi dan Bisnis Islam IAIN Kediri, 2019)
Corporate Social Responsibilityis a concept that a company has various forms of responsibility to all stakeholders including consumers, employees, shareholders, communities and the environment in all aspects of the company's operations that include economic, social, and environmental aspects. Therefore CSR is closely related to